PENGARUH PENDEKATAN WHOLE LANGUAGE TERHADAP KEMAMPUAN MEMBACA SISWA KELAS IV SDN KUNCIRAN 3 KOTA TANGERANG - Esa Denabila; Ahmad Arif Fadilah; Candra Puspita Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the influence of the whole language approach taught on reading comprehension skills in class IV students. This research uses a quasi-experimental research method with a Nonequivalent Control Group Design research design. The population subjects in this study were 60 students in class IV at SDN Kunciran 3, taking samples from two classes, namely class IV A, totaling 30 students, as the control class and class IV B, totaling 30 students, as the experimental class. The data collection technique uses reading comprehension instruments using test questions consisting of 20 pretest questions and 20 posttest questions. The use of the whole language approach has a significant effect on students' reading comprehension abilities at Kunciran 3 Elementary School. To test the hypothesis, the research used a non-parametric test or Mann Whitney test (u test) because one of the data from the control class was not normally distributed or had a sig value. < 0.05. The output obtained is the Mann Whitney test which has been tested to determine the Asymp value. Sig (2-tailed) is 0.00 < 0.05 so the hypothesis in this study is accepted. Thus, at the end of the lesson there was a difference in reading comprehension ability between the control class and the experimental class. Thus, based on the results of research that has been carried out, the whole language approach has an effect and improves the reading comprehension skills of class IV students. Keywords: Reading Ability of Class IV Students, Whole Language.